How do lean and non-lean female collegiate athletes view the eating disorder education they receive from their coaches? - Hines, J. C.; Wendorf, W. L.; Hennen, A. N.; Hauser, K. L.; Mitchell, M. M.; Homa, J. M. (International Journal of Sports Science & Coaching, 2019)
Extant research indicates that collegiate coaches often lack the knowledge or confidence required to provide their student-athletes with effective educational experiences related to eating disorders. The current study investigates the prevalence and quality of such experiences from the perspective of lean and non-lean female student-athletes at a National Collegiate Athletic Association Division III institution. Participants were asked closed- and open-ended questions in an anonymous online survey. Lean and non-lean participants reported similar rates of education despite differential risk for eating disorders. Approximately 70% of student-athletes expressed a desire for a more comprehensive and long-term program of study. Participants` confidence in identifying an eating disorder in a peer did not differ based on type of sport or education status, but those who were educated identified more appropriate potential symptoms than did those who were uneducated. This indicates some degree of educational effectiveness. However, education status and type of sport had no bearing on the likelihood of a participant speaking with their coach about their own or a peer`s potential disorder. Educational attempts were therefore insufficient to help student-athletes overcome the shame and consequential secrecy associated with eating disorders. Our results underscore the need for effective education for at-risk student-athletes while also clarifying that both lean and non-lean student-athletes often want to receive more comprehensive education about eating disorders. Current findings highlight specific areas of student-athlete interest about the topic and could be used to help coaches revise their educational efforts to enhance engagement and long-term retention of information.